Peroxiredoxin6 in Endothelial Signaling - Patel, Priyal (Antioxidants (Basel), 2019)
Peroxiredoxins (Prdx) are a ubiquitous family of highly conserved antioxidant enzymes with a cysteine residue that participate in the reduction of peroxides. This family comprises members Prdx1–6, of which Peroxiredoxin 6 (Prdx6) is unique in that it is multifunctional with the ability to neutralize peroxides (peroxidase activity) and to produce reactive oxygen species (ROS) via its phospholipase (PLA(2)) activity that drives assembly of NADPH oxidase (NOX2). From the crystal structure, a C47 residue is responsible for peroxidase activity while a catalytic triad (S32, H26, and D140) has been identified as the active site for its PLA(2) activity. This paradox of being an antioxidant as well as an oxidant generator implies that Prdx6 is a regulator of cellular redox equilibrium (graphical abstract). It also indicates that a fine-tuned regulation of Prdx6 expression and activity is crucial to cellular homeostasis. This is specifically important in the endothelium, where ROS production and signaling are critical players in inflammation, injury, and repair, that collectively signal the onset of vascular diseases. Here we review the role of Prdx6 as a regulator of redox signaling, specifically in the endothelium and in mediating various pathologies.